Surto de botulismo tipo C em equinos no Rio Grande do Sul - Argenta, Fernando F.; Konradt, Guilherme; Bassuino, Daniele M.; Caprioli, Rafaela A.; Laisse, Cláudio J.M.; Borsanelli, Ana Carolina [UNESP]; Dutra, Iveraldo S. [UNESP]; Driemeier, David (FapUNIFESP (SciELO), 2017)
Botulism in domestic animals is a fatal poisoning caused by ingestion of Clostridium botulinum neurotoxin. This paper describes epidemiological, clinical and laboratorial aspects of a botulism type C outbreak in horses in a farm in Porto Alegre, Rio Grande do Sul. From a total of 20 horses, seven (35%) were affected and died, and one was euthanized after presenting poor prognosis. The horses, which were raised extensively, showed similar clinical signs, that included limited mobility, lethargy, progressive flaccid paralysis, muscle tremors, sweating, ataxia, and frequent falls. Four horses were necropsied and did not show significant macroscopic and microscopic lesions. Brain and spinal cord samples were analyzed by direct immunofluorescence and were negative for rabies. Liver fragments from the four necropsied horses, soil sediment samples, and suspect water from two reservoirs were evaluated by direct exam to verify the botulinum toxin and/or Clostridium botulinum spores presence. In the serum neutralization bioassay in mice, the type C botulinum toxin was detected in one liver sample, at the same time that the soil sediment and water samples were negative in all assays. Based on the epidemiological, clinical and laboratory data the etiological diagnosis of botulism was established by being caused by botulinum toxin type C, and it is suggested that the stagnant water of the dams is the likely source of the toxin.
Outbreak of type C botulism in horses in Rio Grande do Sul
Keywords: Botulinum toxin type C; Botulism type C; Clostridium botulinum; Horses; Poisoning